2008
DOI: 10.1111/j.1743-6109.2007.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient Acute Neurologic Sequelae of Sexual Activity: Headache and Amnesia

Abstract: Introduction Sexual activity may on occasion be complicated by neurologic syndromes of headache and amnesia. These syndromes may be alarming not only to patients but also to medical practitioners unfamiliar with them, initiating inappropriate investigations or advice. Aims To review the clinical features, differential diagnosis, investigation, pathophysiology, and treatment of primary headache associated with sexual activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
3
8
2
Order By: Relevance
“…As in our study, Larner found that men were more frequently affected 7 17. The sudden and severe onset of orgasmic headache means that arterial dissection and subarachnoid haemorrhage should always be excluded 7 17 21. The latter was the second most common sexually triggered neurological emergency in our study.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…As in our study, Larner found that men were more frequently affected 7 17. The sudden and severe onset of orgasmic headache means that arterial dissection and subarachnoid haemorrhage should always be excluded 7 17 21. The latter was the second most common sexually triggered neurological emergency in our study.…”
Section: Discussionsupporting
confidence: 73%
“…The actual incidence of orgasmic headache is unknown 17 20. As in our study, Larner found that men were more frequently affected 7 17.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations